Fred Lesher letters to Thomas H. Kent regarding bird sightings, March 12, 1983 and June 3, 1983 - Lesher, Fredet al (1983)
Two letters from Fred Lesher to Thomas H. Kent regarding bird sightings, March 12, 1983 and June 3, 1983. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1983. Epson - sheet feed/flatbed